MEDIATION RECONSTRUCTION AS ONE OF THE ALTERNATIVE SETTLEMENT OF DECLINE IN THE COURTS BASED ON THE VALUE OF JUSTICE (Study at the Simalungun District Court) - Mariah S.M. Purba; Eman Suparman; Anis Mashdurohatun (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
PERMA No. 1 of 2008 on court mediation procedure is a refinement of the PERMA No. 1 of 2003, concerning the mediation procedure in court. Alternative dispute resolution through mediation aimed at creating a connection or a direct connection between the parties to have the dispute. Based on the above, mediation plays an important role, but in fact the success rate of mediation in court is still very low. I researched this research establishes, that the main problem of the effectiveness of mediation in the District Court in Simalungun and Pematangsiantar, obstacles encountered in the implementation of mediation in state court in the implementation of the mediation solution. The method used in this study is an empirical sociological research study to determine the Effectiveness of law from the perspective of the nature of this research is descriptive. The results of this study show that the effectiveness of mediation is still low to solve dispute. Obstacles encountered in the implementation of mediation in court because the parties did not understand the goodness and benefits of mediation, the role of Advocates less supportive and limitations of a mediator professionals besides facilities mediation process and efforts to overcome it by pursuing the room and mediators were appointed based on considered able to explain the process mediation, and the factors that most substances is the factor structure of the law, legal factors and cultural factors of law, the solution in the implementation of mediation in court additional is expected establishment of the implementation of training and education to become mediators area so as to facilitate legal practitioners, legal academics and legal scholars gain training and education to be a mediator, that mediation can work as expected. Keywords: Mediation, One Alternative, Dispute